Media Tradisional Sebagai Media Komunikasi Pembangunan Masyarakat Titidu Gorontalo - Mohamad Hasan As'adi (UIN Sunan Kalijaga Yogyakarta, 2020)
Communication media as a means to convey information is traditional and modern. The rapid development of communication technology in modern media by some communication experts is allegedly able to change the traditional form of communication found in Indonesia. The author is interested to know the benefits of the implementation of the Gorontalo tribal tradition as a traditional communication media play a role in development in the village of Titidu? By using the method of observation and in-depth interviews with 34 sources obtained from purposive sampling techniques. This study was also complemented by a literature review to deepen data and data processing using descriptive qualitative analysis. The findings show the existence of traditional media that still survive in the village of Titidu aims to preserve the traditions of the Gorontalo tribal people who place the tradition based on syara 'and syara' based on the book of God as a way of life, so that the culture of Gorontalo people highly values traditions especially those with Islamic nuances. The tradition is related to customs in the form of wedding ceremonies, coronation and reception of officials, funerals, hair cutting and weighting. Art in the form of remembrance (obeyed), burdah (buruda), funds and zamrah. Dance movements or sports such as langga, longgo, and literature in the form of prose and poetry. By implementing interpersonal, group, free and social communication to socialize regional development in the fields of innovation (health, education, national defense, arts, development), government policy, program accountability in the village head's remarks.Media komunikasi sebagai sarana untuk menyampaikan informasi bersifat tradisional dan modern. Pesatnya perkembangan teknologi komunikasi pada media modern oleh beberapa pakar komunikasi disinyalir dapat merubah bentuk komunikasi tradisional yang terdapat di Indonesia. Penulis tertarik untuk mengetahui manfaat pelaksanaan tradisi suku Gorontalo sebagai media komunikasi tradisional berperan dalam pembangunan di Desa Titidu. Dengan menggunakan metode observasi dan wawancara mendalam terhadap 34 narasumber yang di dapat dari teknik sampling purposive. Penelitian ini juga dilengkapi dengan kajian pustaka untuk memperdalam data serta pengolahan data menggunakan analisis deskriptif kualitatif. Temuan menunjukkan keberadaan media tradisional yang masih bertahan di Desa Titidu bertujuan untuk melestarikan tradisi masyarakat suku Gorontalo yang menempatkan adat bersendikan syara’ dan syara’ bersendikan kitab Allah sebagai pandangan hidup, sehingga secara kultural masyarakat Gorontalo sangat menghargai tradisi-tradisi terutama yang bernuansa Islami. Tradisi tersebut berhubungan dengan adat istiadat berupa upacara pernikahan, penobatan dan penyambutan pejabat, pemakaman, pengguntingan rambut serta pembeatan. Kesenian berupa dzikir (diikili), burdah (buruda), dana-dana dan zamrah. Gerak atau olahraga tarian seperti langga, longgo, dan sastra berupa prosa maupun puisi. Dengan menerapkan komunikasi antar pribadi, kelompok, bebas dan sosial untuk mensosialisasikan pembanguan daerah pada bidang inovasi (kesehatan, pendidikan, bela negara, kesenian, pembangunan), kebijakan pemerintah, pertanggungjawaban program dalam sambutan kepala desa.